Nobody cares about us: COVID-19 and voices of refugees from Aotearoa New Zealand. Issue 4 (2nd October 2021) - Jayan, Pooja; Dutta, Mohan J.
ABSTRACT: Aotearoa New Zealand's pandemic communication approach amidst the COVID-19 (C19) has been applauded around the world. The New Zealand government's border controls and other measures in response to C19 impacted refugees at the margins and prevented people from accessing support services and healthcare. The sanctioned power to 'care' thus became a performative form of power for silencing through the dismissing of voices of refugees as being irrelevant. Experiences of refugees at the margins are constructed amid the erasure of community voices in dominant approaches to health. What was missing from the dominant discourses was the voice of the refugees, who had gone through painful experiences of displacement and resettlement. How did the refugee communities at the margins of Aotearoa New Zealand navigate through the prevailing structural impediments to health during the pandemic? In this study, we use a culture- centred analysis to centre the structural context of disenfranchisement during the COVID-19 lockdown. Drawing on in-depth interviews with refugee participants, we attend to how health is negotiated in the midst of the COVID-19 outbreak and lockdown response at the margins. Infectious diseases such asC19 lay bare the structural determinants that create health and well-being challenges among refugee communities in New Zealand. The narratives point out that the one-size-fits-all approach of the government left behind refugees at the margins during the C19 in the public health efforts.